2017
DOI: 10.1136/bmj.j1131
|View full text |Cite
|
Sign up to set email alerts
|

Impact of total knee replacement practice: cost effectiveness analysis of data from the Osteoarthritis Initiative

Abstract: ObjeCtivesTo evaluate the impact of total knee replacement on quality of life in people with knee osteoarthritis and to estimate associated differences in lifetime costs and quality adjusted life years (QALYs) according to use by level of symptoms. DesignMarginal structural modeling and cost effectiveness analysis based on lifetime predictions for total knee replacement and death from population based cohort data.setting Data from two studies-Osteoarthritis Initiative (OAI) and the Multicenter Osteoarthritis S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
134
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(138 citation statements)
references
References 55 publications
3
134
1
Order By: Relevance
“…The prevalence of OA is on the rise and it is expected to be continuing increase in the coming decades due to the longevity and the growing prevalence of obesity (Wirth et al, ). A number of risk factors attribute to the development of OA, such as genetic factors, diabetes, obesity, joint infections, and damages from mechanical stress (Ferket et al, ). The management of OA includes weight control, physical activity, medications, joint replacement surgery, and a variety of other techniques (Groen, Diloksumpan, van Weeren, Levato, & Malda, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of OA is on the rise and it is expected to be continuing increase in the coming decades due to the longevity and the growing prevalence of obesity (Wirth et al, ). A number of risk factors attribute to the development of OA, such as genetic factors, diabetes, obesity, joint infections, and damages from mechanical stress (Ferket et al, ). The management of OA includes weight control, physical activity, medications, joint replacement surgery, and a variety of other techniques (Groen, Diloksumpan, van Weeren, Levato, & Malda, ).…”
Section: Introductionmentioning
confidence: 99%
“…A number of risk factors attribute to the development of OA, such as genetic factors, diabetes, obesity, joint infections, and damages from mechanical stress (Ferket et al, 2017). The management of OA includes weight control, physical activity, medications, joint replacement surgery, and a variety of other techniques (Groen, Diloksumpan, van Weeren, Levato, & Malda, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This in turn impacts the cost effectiveness and clinical impact of these procedures. 6 The role of psychological factors with regard to successful surgical outcomes has been highlighted previously. 7 For example, patients undergoing TKA with preoperative psychological distress are more likely to be more dissatisfied and have worse pain postoperatively.…”
Section: Introductionmentioning
confidence: 95%
“…With the increasing numbers of procedures, the burden of patients with poor outcomes will also continue to increase. This in turn impacts the cost effectiveness and clinical impact of these procedures …”
Section: Introductionmentioning
confidence: 99%
“…Younger patients undergoing primary TKR are also far more likely to require revision surgery in the future due to increased demands and expectations following surgery [6]. Furthermore, a recent analysis performed by Ferket et al found that current practice on TKR operations leads to minimal changes in quality of life and quality adjusted life years, and is only cost-effective in older patients with severe symptoms [7]. For these reasons TKR should ideally be delayed for as long as reasonably possible and initially managed conservatively.…”
Section: Introductionmentioning
confidence: 99%